Художня публіцистика як джерело емпіричного матеріалу для лінгвістичних досліджень - Самойлова, І. (Лексикографічний бюлетень, 2015)
The article underlines the importance of journalistic texts as a source of empirical data for linguistic research. The lexical neoplasms in media texts by Ivan Dziuba were considered. In accordance with the methods of derivation of the extracted words are combined into groups. To identify the types of derivational affi xal derivatives for the specifi ed source words. Lexemes were considered, which are formed on the same type, but with diff erent temporal perspectives on adaptation in the language.